Rapid assessment of the riparian zone habitat of river - R.A.L. Amper; G.R. Puno; R.C.C. Puno (Global Journal of Environmental Science and Management)
Some riparian areas of the country are in danger of deterioration due to uncontrolled exploitation coupled with loose implementation of environmental protection policies and regulations. Muleta River, a major watershed in Bukidnon, Philippines, was assessed to determine the present condition of its riparian habitat. Abiotic and biotic conditions of the river were assessed. Other factors including land cover, population density, and river geomorphologic characteristics contributing to the river condition were also evaluated. Results revealed that Muleta Watershed is in sub-optimal condition signifying favorable condition for floral and faunal habitat. However, considerable degradation in some isolated cases was likewise spotted. Biotic condition has shown greater degradation approaching marginal condition compared to the abiotic condition which is yet in the upper sub-optimal condition. It was found out that the midstream portion of the watershed is the most disturbed, followed by the downstream area and lastly by the upstream portion. The extent of agricultural cultivation is found as one of the significant factors affecting the health of the riparian habitat areas. It is recommended that riparian protection policies must be formulated and implemented to abate, if not prevent, the impact of anthropogenic interventions resulting to overexploitation in the riparian areas especially in midstream portion of the river.